Assessing Regional Asset Management “Operational Standards” at the Regional Development Planning Office of West Sulawesi Province - Kartini Kartini; Mediaty Mediaty; Ermayanti Ermayanti; Marwa Naazla; Mohammad Rizvan Dwi Putra Darman; Yulius Tandigoa (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
Effective local government asset management is critical for the efficient operation and sustainability of public institutions regarding their responsibility and otonomy given by the central government of Indonesia. On local government level, Regional Development Planning Office (Bappeda) is responsible as asset managers on province level. This study evaluates the management of regional assets at the Bappeda Office of West Sulawesi Province. Data collected through survey and interview with the office representatives and employee, supplemented by literature analysis of Domestic Affairs Regulation Number 19 Year 2016 to evaluates the policy implementation in the office. Data suggest that current activities or policy implementation in the office are alligned as the national policy standards. Core acts in the office includes planning – budgeting, procurement, utilization, optimization, security – maintenance, assessment, transfer, disposal, deletion, administration, guidance – supervision – control, and compensation – sanctions. The practices align with the Ministry of Domestic Affairs Policy, ensuring correct and effective implementation. Out of 100, we scored 58 - 59 to the current conformity level at Bappeda office. Some challenges remain with end-users, as some desire to personally own the official vehicles, occasionally breaching the rules, ownership, disposal, etc. The study underscores the importance of following established asset management cycles and regulations for effective asset utilization and maintenance, while highlighting the need for strategies to improve user compliance.